Practitioner Profile: An Interview with Barbara Mitchell, LCSW - Barbara Mitchell (Journal of Financial Therapy, 2012)
Barbara Mitchell, LCSW is a clinical social worker and certified Imago Relationship Therapist who has maintained a private practice in New York City for over 30 years. Her work in the addictions field, which is informed by self-psychology and a 12-Step approach, led her to the discovery that one’s relationship to money can be transformed from self-destructive to life-enhancing.
Keywords: social work; financial therapy